Creation and Psychometric Validation of the Sexual Minorities and Prostate Cancer Scale (SMACS) in Sexual Minority Patients-The Restore-2 Study. Issue 3 (4th February 2022) - Polter, Elizabeth J.; Kohli, Nidhi; Rosser, B.R. Simon; Talley, Kristine M.C.; Wheldon, Christopher W.; Hoefer, Chris J.; Wright, Morgan; Haggart, Ryan; Mitteldorf, Darry; Kilian, Gudrun; Konety, Badrinath R.; Ross, Michael W.; et al.
ABSTRACT: Background: Existing measures of sexual functioning in prostate cancer survivors focus primarily on erectile function and do not adequately measure the experiences of sexual minority men. Aim: To develop and psychometrically evaluate a new scale to measure sexual functioning among sexual minority men with prostate cancer. Methods: Sexual minority prostate cancer patients (n = 401) completed an online battery of urinary and sexual functioning tests in 2019, including a new 37-item instrument about their sexual functioning post-treatment for prostate cancer. Outcomes: We used confirmatory factor analysis to determine the construct validity of a new scale including five subscales: a four-factor model for all participants (n = 401) evaluated Sexual Satisfaction, Sexual Confidence, Frequency of Sexual Problems, and Urinary Incontinence in Sex. A single-factor model completed only by participants who had attempted or desired receptive anal sex (n = 255) was evaluated in the fifth subscale: Problematic Receptive Anal Sex. To evaluate criterion validity, we calculated the intercorrelations between each Sexual Minorities and Prostate Cancer Scale (SMACS) subscale and four related scales: the Expanded Prostate Cancer Index Composite-50 (EPIC), the Functional Assessment of Cancer Therapy-Prostate, the Brief Symptom Inventory-18, and the International Consultation on incontinence questionnaire. Cronbach's alphas were calculated to measure internal consistency (ie, reliability). Results: Cronbach's alpha values ranged from 0.64 to 0.89. Loadings (0.479–0.926) and model fit indices were strong (Root Mean Square Error of Approximation: 0.085, Standardized root mean squared residual: 0.063, comparative fit index: 0.927, Tucker-Lewis Index: 0.907). For criterion validity, Sexual Satisfaction, Sexual Confidence, and Frequency of Sexual Problems were moderately correlated with EPIC function and bother scores (r = 0.50–0.72) and Urinary incontinence in sex correlated moderately with EPIC Urinary Function and International Consultation on incontinence questionnaire scores (0.45–0.56). Clinical Implications: The SMACS can be used by clinicians and researchers to comprehensively measure sexual functioning in sexual minority men, in conjunction with existing scales. Strengths and limitations: This new scale is validated in a large, geographically diverse cohort of sexual minority cancer survivors and fills an important gap in existing measures of sexual functioning. Limitations include a lack of a validation sample. Conclusion: The SMACS is a valid and reliable new scale that measures sexual minority men's experience of urinary incontinence in sex, problematic receptive anal sex, and sexual distress.